Ionic thermopower of composite electrolytes - Vennekamp, Martin; Janek, Jürgen; Justus Liebig University Giessen (My University, 1999)
The ionic thermopower of solid electrolyte composites which are composed of a solid electrolyte and an electrically insulating inert phase is analyzed. For a stoichiometric model system AX with Frenkel disorder in the cation sublattice we derive formal relations within a lattice point defect model for the change in ionic thermopower on dispersing the second phase. It is shown that thermopower measurements may provide information on the defect concentrations in the space charge regions surrounding the inert phase. Available experimental results are discussed.
Keywords: Thermopower; Solid electrolytes; Ionic conduction; Interfaces; Space charges; ddc:540